The state of circulation of the lower troposphere in the Austral polar region in the period of recent warming - Martazinova, V. F.; Ivanova, Ye. K.; Tymofeyev, V. E. (Ukrainian Antarctic Journal, 2008)
Atmospheric circulation in Antarctic region is studied by means of mean sea level pressure fields for each decade during 1961–2000 as well as most probable synoptic processes for winter and summer seasons, 1991–2000. Present-day state of atmospheric circulation is represented by predominant cyclones especially at Bellinsghausen Sea. Westerlies and north-westerlies towards Graham Land are prevailing, decreasing probability of cold air inflow from the Antarctic continent and explaining significant multi-years’ near-surface air temperature growth in the region of the Antarctic Peninsula, including Ukrainian base of Academic Vernadsky. Results of our study let us to better understand present-day state and reasons of climate change (warming) in this region.